Construction and design manual : architectural renderings - Schillaci, Fabio ([Place of publication not identifed] : PageOne, 2009)
Fourteen major international rendering studios present a selection of their work, together with comments on their methodology and use of digital technology. As a standard work on architectural rendering, this book traces the history and along the way rehabilitates this occupation as an independent discipline in the broad sphere of architecture. The book contains a comprehensive overview from the earliest architectural drawings through to modern, highly technical forms of digital rendering, and includes tutorials based on everyday practice and essays by renowned experts.
Theory: Drawing between history and digital innovation/ Fabrizio Avella -- Architectural drawing in the age of its electronic reproducibility / Augusto Romano Burelli -- Do we lose the hand? / Fabio Schillaci -- Practice: Offices: Simon Jones & Associates -- Lee Dunnette -- Dennis Allain -- Kirk Fromm -- ArtandDesignStudios.com -- Andy Hickes -- Labtop Rendering -- Rendertaxi -- Studio AMD -- Federico Pitzalis -- Marco Giovanni De Angelis -- ArtefactoryLab-- Pure -- Stac! Studios -- Notes: The making of a render / Fabio Schillaci.
Keywords: ARCHITECTURAL DRAWING -- HISTORY